Recurrence of cardiac arrhythmias after taking rifampicin in a patient who also co-tread with atenolol - Protopapas, Andreas; Lambrinou, Ekaterini (My University, 2020)
Background: Previous studies have discussed various aspects of the metabolism of rifamicin and its effects on the action of other drugs. The interaction of rifampicin with cardiovascular drugs seems to cause significant clinical effects. Aim: The purpose of this case report is to show the risk of potentially serious interaction when rifampicin is concomitantly administered with other drugs, and particularly with atenolol. Case presentation: A 63-year-old male was diagnosed with staphylococcal infection in the left arm and was initially treated with rifampicin. The patient had history of hypertension and cardiac arrhythmias (premature ventricular contraction-PVC) for which he received ramiril and atenolol. Upon admission to the hospital, the electrocardiogram recorded a sinus rhythm without the presence of PVCs. Five days after receiving rifampicin, the patient showed multiple PVCs that some-times occurred in pairs. Rifampicin was discontinued and replaced with Oxacillin. PVCs decreased in frequency, a few days after the discontinuation of rifampicin. Conclusion: As reports of rifampicin interactions with other medicines are constantly on the rise, health professionals should be aware of this informing the patients and ask-ing to contact them immediately when this happen. Atenolol and other β-blockers when co-administered with rifampicin, the patient should be monitored closely for signs of deregulation, as action and therapeutic efficacy are reduced.
Keywords: Atenolol; Drugs interaction; Rifampicin